The office. Season eight [videorecording (DVD)] - Daniels, Greg; Gervais, Ricky; Merchant, Stephen; Wilson, Rainn, 1966-; Krasinski, John, 1979-; Fischer, Jenna, 1974-; Kaling, Mindy; Helms, Ed (Universal Studios Home Entertainment, 2012)
Big changes are ahead for Dunder Mifflin/Sabre, with Robert California as the new CEO. Andy is promoted to Regional Manager, with Dwight his number two. Jim and Pam are expecting their second child, and Angela is pregnant with her first.